Third-Party Trackers in COVID-19 Mobile Applications Can Enable Privacy Leaks - Serrano, Nicolas; Betarte, Gustavo; Campo, Juan Diego (Anais do Latin-American Symposium on Dependable Computing (LADC); 2023: Anais do XII Latin-American Symposium on Dependable Computing, 2023)
Since 2019, the world has been facing an unprecedented pandemic. Governments and various organizations have made great efforts to develop applications that aid in controlling the spread of COVID-19 and improve people’s quality of life. However, our research has discovered that many of these applications contain third-party libraries, including trackers, which can impact user privacy. Out of the 595 applications we reviewed, 402 included at least one tracker, and sensitive information was being transferred to these tracker servers. From a privacy perspective, including trackers in sensitive applications must be reconsidered, primarily when governments sponsor them.